Training on Creating Functions using GeoGebra at SMAN 5 Jember - Merysa Puspita Sari; Ainurrofiqoh, Dewi Ika; Zahro, Millatuz; Mulyaningsih, Woro; Helmi, Muhammad Lutfi (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2025)
Mathematics education at the Senior High School level plays an important role in forming the foundational understanding of more complex mathematical concepts, one of which is algebraic function graphs. Despite its importance, many students face difficulties in understanding and drawing algebraic function graphs due to the limitations of traditional teaching tools. GeoGebra, a computer-based mathematics application, can be a solution to address this issue. GeoGebra offers advanced visual aids, allowing students to draw and analyze graphs interactively. The use of GeoGebra makes it easier to visualize various elements of graphs, such as intersection points, slopes, and extrema, and allows students to conduct experiments by manipulating function parameters. The aim of this community service activity is to introduce the concept of algebraic function graphs, teach the use of GeoGebra as a visual aid, and enhance students' analytical skills and learning motivation at SMAN 5 Jember. The methods applied includes the socialization and introduvtion of GeoGebra, interactive workshops, independent practice, and student understanding evaluation. The results of this activity show that students are more motivated and have a better understanding of algebraic function graphs after using GeoGebra. Therefore, the use of GeoGebra can be an effective alternative for teaching complex mathematical concepts at the Senior High School level.